Human, all too human, transhuman: Nietzsche's challenge to humanism - Heit, Helmut (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Nietzsche mocks humanism at various occasions, in part because of his naturalized anthropology. But concepts of self-overcoming, refinement, and liberation are regularly present in his writings. This paper argues that the connection between the naturalist and the perfectionist aspects in Nietzsche's thought derive from the 'mysterious double-character' of human nature and result in a political anthropology of freedom. The first section explains Zarathustra's talk of the Over-Human not as a doctrine or a commandment, but as persuasion and invitation to attempt a higher development of humanity. The second section shows how Nietzsche uses his readings of contemporary physiology to develop a conception of the human as a dynamic body-organization. In the third section, it is argued that the natural- and cultural-historical development of the human species has created a possibility for further conscious transformation. The design an aesthetically approvable character is neither naturally determinated nor morally required, but results from a - as I call it – ‘normative force of the possible’, which can be realized through cultural exercise. Nietzsche's challenge to humanism is an invitation to become better humans.